Introducing the Lipidomics Minimal Reporting Checklist - McDonald, Jeffrey G.; Ejsing, Christer S.; Kopczynski, Dominik; Holčapek, Michal; Aoki, Junken; Arita, Makoto; Arita, Masanori; Baker, Erin S.; Bertrand-Michel, Justine; Bowden, John A.; Brügger, Britta; Ellis, Shane R.; et al. (Nature metabolism, 2022)
The rapid increase in lipidomic data has triggered a community-based movement to develop guidelines and minimum requirements for generating, reporting and publishing lipidomic data. The creation of a dynamic checklist summarizing key details of lipidomic analyses using a common language has the potential to harmonize the field by improving both traceability and reproducibility.